Pengaruh Kredit UMKM Terhadap Tingkat Pengangguran Terbuka Kabupaten/Kota di Provinsi Jawa Barat Tahun 2015-2019 - Yogi Juniarto; Siti Muchlisoh (Seminar Nasional Official Statistics, 2021)
Unemployment is one of the problems that are always faced by a country, including Indonesia. Micro-business have emerged as one of the most developed jobs in Indonesia. With the continued growth of the number of micro-business in Indonesia, there is a policy of providing micro-credit with the hope that micro-business can grow and be able to open more new jobs, so that the unemployment rate can be suppressed. West Java Province is one of the three provinces that have the highest number of micro-credit in Indonesia. This study aims to identify whether the provision of micro-credit can have a significant effect in reducing the unemployment rate in West Java. Based on the results of the study using the panel data regression method with the FEM SUR model, it was found that the provision of micro-credit significantly succeeded in reducing the unemployment rate in West Java.